2018
DOI: 10.1002/cphc.201701322
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Infrared Spectrum of 5‐Bromo‐2,4‐pentadiynenitrile from a CCSD(T)/B3LYP Anharmonic Potential

Abstract: On the grounds of a hybrid CCSD(T)/B3LYP/aug-cc-pVTZ anharmonic potential and the use of a variational and variational-perturbational methods, the IR spectra of 5-bromo-2,4-pentadiynenitrile (BrC N) is revisited in the mid-infrared region up to 4500 cm . A position and intensity analysis of our theoretical results allow us to assign the fundamental bands together with their combinations and overtones, in the aforementioned range of frequencies. The main objective of this work is to give an "a priori" complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A fourth approach has been applied to acetonitrile and other systems by Pouchan and co-workers. This entails first the determination of CCSD­(T) harmonic frequencies and normal coordinates and then the direct evaluation of cubic and quartic force constants, in those normal coordinates, at a lower level of theory. In their work, their lower level of theory involves DFT.…”
Section: Methodsmentioning
confidence: 99%
“…A fourth approach has been applied to acetonitrile and other systems by Pouchan and co-workers. This entails first the determination of CCSD­(T) harmonic frequencies and normal coordinates and then the direct evaluation of cubic and quartic force constants, in those normal coordinates, at a lower level of theory. In their work, their lower level of theory involves DFT.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently C. Pouchan [16] published the theoretical modelling of the HC3N vibrational spectrum by comparing a DFT molecular dynamics (DFT/MD) approach with a static anharmonic approach under the assumption of a vibrational second order perturbative treatment (VPT2). This study, limited to fundamental frequencies only, showed that the DFT harmonic calculations from a B3LYP functional [17] associated with a 6-31+G (d,p) base did not reflect, unlike many other systems previously studied [18][19][20][21][22][23][24][25], the harmonic results obtained at the CCSD(T) [26]/aug-cc-pVTZ [27]level, and that the potential function limited to the order 4 did not allow to give accurate VPT2 anharmonic wavenumbers to reproduce the first harmonic bands of the lowest frequencies and their combinations.…”
Section: Introductionmentioning
confidence: 56%
“…For electronic computations, we used GAUSSIAN 16 suite [26] of programs, and for VPT2 [27] vibrational calculations, we used the MOLPRO 2018 [28] package. Finally, the VPT2 vibrational results with the hybrid CCSD(T)-F12b/B3LYP PES are obtained with our VPT2-CI program [29][30][31][32]. In a second step, we computed the IR spectrum at the VCI level with a complete ab initio PES obtained with the CCSD(T)-F12b/MP2-F12 potential.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%